Correlation of Body Mass Index and Waist/Hip Ratio with Glycated Hemoglobin in Prediabetes - Bala, Manju (EJIFCC, 2019)
INTRODUCTION: Prediabetes (preDM) is a state of disordered glucose metabolism rather than a distinctive clinical entity representing an interim condition and a risk factor for the development of diabetes. Diagnosis of asymptomatic people to assess the risk for development of DM should be done in overweight or obese adults (BMI ≥ 25 kg/m(2)) of any age along with person having one or more additional risk factors like physical inactivity, first degree relative with DM, high risk race/ethnicity, hypertension etc. OBJECTIVES: To correlate glycated hemoglobin (HbA(1c)) levels with body mass index (BMI) and waist hip ratio (WHR) in prediabetic patients. MATERIALS & METHODS: The present case control study was performed at Pt. B. D. Sharma PGIMS, Rohtak includes thirty prediabetic patients of age group 20-40 years diagnosed on the basis of HbA(1c) (5.7-6.4%). Thirty healthy and age matched control were taken. After taking written consent, they were subjected to physical examination and anthropometric measurements as per protocol and findings were noted. Venous blood sample was withdrawn for estimation of HbA(1c) levels. RESULTS: The correlation coefficient between BMI (27.01 ± 2.91 kg/m(2)) and HbA(1c) (5.94 ± 0.21%) is r = 0.583 with p value = 0.001 and between WHR (0.87 ± 0.38) & HbA(1c) is r = 0.495 with p value = 0.005. Both BMI & WHR are positively correlated with HbA(1c). CONCLUSION: Obesity is a risk factor for glycation of hemoglobin & hence, it is an effective measure for prevention of prediabetes and diabetes.